Djaara cultural authority drives inclusion of their knowledge and culture in a Joint Management Plan for parks. (28th January 2022) - Carter, Rodney; Atkinson, Graham; Burchill, Marlene; Phillips, Rebecca; Humann, Doug; Mahoney, Jan; Miles, Trevor; Braid, Michele; Buissereth, Rachel; Cowell, Stuart; Hill, Rosemary; Huggins, Barbara; et al.
Summary: Six parks in central Victoria were handed back to ownership of Dja Dja Wurrung People ( Djaara ) as part of the Recognition and Settlement Agreement 2013 with the State of Victoria. Dhelkunya Dja Land Management Board (DDLMB) developed a Joint Management Plan (JMP) for these parks, which was approved under Victorian legislation and launched in October 2018. Here, we show how and why Djaara used their cultural authority to ensure their knowledge, and culture was incorporated into the JMP. Djaara's cultural authority produced significant innovations. First, the unique Free, Prior and Informed Consent (FPIC) processes implemented by the Dja Dja Wurrung Clans Aboriginal Corporation (DDWCAC) for the DDLMB ensured that shared governance and decision‐making underpinned joint management. Second, the participatory Healthy Country Planning approach enabled greater equity, including a unique 3‐day 'Map‐a‐Thon' that integrated cultural and natural spatial data. Third, the challenge of achieving power‐shifting from the government to the Djaara was addressed through a relationship‐based approach, supported by systematic, evidence‐based planning. The DDLMB and DDWCAC ensured development of the final JMP was innovative, equitable, culturally appropriate and culturally informed. Future processes would be improved by legislative change to mandate FPIC, with substantially greater resources to support the FPIC processes, and the inclusion of a 'planning to plan' stage to allow all participants to gain the capacities needed. Supporting the cultural authority of Traditional Owners provides a new direction that has much to offer planning for other joint‐managed parks in Victoria and elsewhere.